2020
DOI: 10.1093/jn/nxz215
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Dietary Fish Oil Reduces Adiposity and Mitigates Bone Deterioration in Growing C57BL/6 Mice Fed a High-Fat Diet

Abstract: Background Intake of total fat is linked to obesity and inversely associated with bone density in humans. Epidemiologic and animal studies show that long-chain n–3 (ω-3) PUFAs supplied as fish oil (FO) are beneficial to skeletal health. Objective This study tested the hypothesis that increasing dietary FO would decrease adiposity and improve bone-related outcomes in growing obese mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Dietary supplementation with long-chain n-3 (ω-3) PUFAs, supplied as fish oil (FO), which is known for its antiinflammatory effects, demonstrated to be beneficial for skeletal health, as evidenced by increased osteogenesis and decreased osteoclastogenesis (179,180). A recent study by Cao et al (192) reported that 6 months of a FO diet increased bone density and microstructure. However, they did not investigate bone adiposity or inflammatory responses in BM in these conditions.…”
Section: Life-style Interventions: Dietary and Physical Activity Intementioning
confidence: 99%
“…Dietary supplementation with long-chain n-3 (ω-3) PUFAs, supplied as fish oil (FO), which is known for its antiinflammatory effects, demonstrated to be beneficial for skeletal health, as evidenced by increased osteogenesis and decreased osteoclastogenesis (179,180). A recent study by Cao et al (192) reported that 6 months of a FO diet increased bone density and microstructure. However, they did not investigate bone adiposity or inflammatory responses in BM in these conditions.…”
Section: Life-style Interventions: Dietary and Physical Activity Intementioning
confidence: 99%
“…In addition, ALP is a key enzyme marker of bone formation due to its action in regulating the process of biomineralization [29]. Previous studies have shown that the expression level of ALP decreased in 6-week-old male C57BL/6 mice fed a high-fat diet for 6 months [30].…”
Section: Discussionmentioning
confidence: 99%
“…and bone mass of second lumbar vertebrae and lower femoral Tb.Sp. [ 75 ]. In contrast, no differences in femur BMD or biomechanical strength properties were found in forty-day-old male Sprague–Dawley rats maintained for 65 days on HFDs containing coconut oil, flaxseed oil or safflower oil or a standard diet.…”
Section: Dietary Lipids and Bone Healthmentioning
confidence: 99%